Optimal Power Management via Dynamic Power Pools in DC MG Clusters - Makarand S. Ballal; Shivpal R. Verma; Sarvesh A. Wakode; Hiralal M. Suryawanshi (IEEE Access)
This paper introduces a methodology for managing and controlling microgrid (MG) clusters through the establishment of diverse power pools and optimizing resource allocation based on available generation. The proposed algorithm, incorporating equivalent droop control, facilitates integrated economic optimization by the MG cluster operator (MCO), considering market participation through generation and consumer bids. The methodology dynamically adapts to fluctuations in power generation and consumer demand, ensuring effective power management with reduced control complexity. Real-world feasibility is demonstrated through Hardware-in-the-Loop (HIL) experiments on an off-grid MG cluster, leveraging RT-LAB and Xilinx Kintex-7 FPGA.